The Tapis Kapal Motif: A Preservative of Lampung’s Decorative Arts at The Krakatau Festival Stage - Putri, Giovanni Arissa; Wahyudi, Tri (Gorga : Jurnal Seni Rupa, 2025)
The province of Lampung has a rich cultural heritage, including Tapis, a traditional textile art featuring the ship motif. Tapis plays a vital role in traditional ceremonies, but its presence is declining in society. This indicates challenges in its preservation amid modernization. To address this, efforts to sustain Tapis with ship motifs are applied through the Krakatau Festival, an annual event in Lampung. This study aims to raise awareness of Lampung’s decorative arts preservation and explain the philosophy behind Tapis with ship motifs through the festival. The research employs a qualitative approach, analyzing design elements such as shape and color, along with the Art Deco style. Data collection techniques include observations, interviews, field notes, and documentation. The study was conducted at Way Halim Sports Center (PKOR) in Bandar Lampung during the Krakatau Festival on July 8, 2023, and at the Lampung Pavilion in TMII, Jakarta. The findings highlight the implementation of ship motif Tapis ornaments on the festival stage design. The results indicate that applying Tapis ship motifs to the stage and art installations enhances cultural significance, creating an authentic atmosphere and strengthening visitors’ connection to Lampung’s heritage. Additionally, this initiative contributes to preserving Lampung’s decorative arts, reinforcing its national identity as part of Indonesia’s cultural richness. The Krakatau Festival serves as a platform to promote and sustain this traditional art for future generations.